Prevalence and determinants of Soil-Transmitted Helminths among urban vegetable farmers in Ghana. - Gerard Quarcoo; Samuel Armoo; Augustina Angelina Sylverken; Matthew Glover Addo (PLoS ONE)
Introduction Urban vegetable farmers in Ghana face multiple health risks, including soil-transmitted helminths (STHs), which may contribute to morbidities that threaten urban food security. Additionally, infected farmers may act as persistent sources of disease transmission within urban populations. There is the need to assess the burden of STH among these farmers using more sensitive molecular assays. Methods This was a cross-sectional study involving 168 urban farmers from Accra and Tamale in Ghana's Greater Accra and Northern regions, respectively. Participants completed semi-structured questionnaires, and stool samples were collected for analysis. A qualitative Polymerase Chain Reaction (QPCR) assay was employed to detect STH prevalence, targeting the ITS1, ITS2, and 18S genes of Ascaris lumbricoides, Ancylostoma duodenale and Strongyloides stercoralis, respectively. Results While no positives were found in Tamale, 5.1%, 2.5%, and 0.8% of participants in Accra tested positive for A. lumbricoides, A. duodenale and S. stercoralis, respectively. Inadequate use of Personal Protective Equipment (PPEs) and STH infection status were strongly correlated among risk factors (Odds ratio; 4.3, 95% Cl: 1.03-18.00, p-value = 0.04). Overall, 72% of participants in Tamale wore PPEs, compared to 43% in Accra. Conclusions Even though STH was not common, inadequate PPE use was a major factor in STH transmission in urban vegetable farms. Therefore, the key to drastically lowering the STH burden in urban farms is education and behaviour changes. Using more sensitive molecular diagnostic assays is crucial in low prevalence environments.